Flabby Ridge Correction Using an Auxiliary Technique With Connective Tissue Graft - Matida Hamata Saito, Celia Tomiko [UNESP]; Luvizuto, Eloa Rodrigues [UNESP]; Bosco, Álvaro Francisco [UNESP]; Goiato, Marcelo Coelho [UNESP]; Barioni, Sônia Regina Panzarini [UNESP] (Lippincott Williams & Wilkins, 2012)
A common finding in patients with edentulous maxilla and partially dentate mandible is mainly the presence of flabbiness in the anterior edentulous alveolar ridge that can compromise the retention and stability of a denture. Thus, this case report presents the correction of a flabby ridge, using an auxiliary technique combining surgical excision and autogenous connective tissue grafting. The technique improved the quality of the osteomucosal support of the alveolar ridge and increased the vestibule deepness, whose result increased the success rate of the new conventional total prosthesis.
Keywords: Alveolar ridge; alveolar ridge resorption; preprosthetic surgery